Consumption of Omega 3 (N-3) as a factor for cardiovascular disease prevention - Ferreira, Gildete Rezende (2012)
Some studies have shown a positive association between saturated fat intake and the prevalence of cardiovascular diseases, as well as a negative association with the intake of unsaturated fats. These studies indicate a change in the recommendations of fatty acids, by better use of and subject to an adequate diet in order to reduce the prevalence of cardiovascular diseases. Currently, it is assumed that the conditions and exposure to risk factors (sedentary, overweight, obesity, smoking and diseases of the circulatory system) whose association with cardiovascular disease (CVD) has sufficiently demonstrated (elevation of serum lipids and its fractions, glucose and blood insulin, blood pressure, thrombogenic factors, obesity, smoking and physical inactivity, among others) have a potentiating effect between them. The biological attributes such as age and gender, can not be modified, however, other genetic risk factors that are modifiable either relate to the environment. Over the past 30 years, attention has focused increasingly on the relationship between nutrition and cardiovascular disease. The literature shows that obesity was positively associated with risk of developing CDV, becoming one of the most significant risk factors, so that the weight loss and prevention of weight gain have to be considered one of the most important strategies to reduce the incidence of CVD. And it has close relationwith the type of feed consumed.